Challenges at work and financial rewards to stimulate longer workforce participation - Beek Allard; Deeg Dorly JH; Proper Karin I (BMC, 2009)
Abstract Background Because of the demographic changes, appropriate measures are needed to prevent early exit from work and to encourage workers to prolong their working life. To date, few studies have been performed on the factors motivating continuing to work after the official age of retirement. In addition, most of those studies were based on quantitative data. The aims of this study were to examine, using both quantitative and qualitative data: (1) the reasons for voluntary early retirement; (2) the reasons for continuing working life after the official retirement age; and (3) the predictive value of the reasons mentioned. Methods Quantitative data analyses were performed with a prospective cohort among persons aged 55 years and older. Moreover, qualitative data were derived from interviews with workers together with discussions from a workshop among occupational physicians and employers. Results Results showed that the presence of challenging work was among the most important reasons for not taking early retirement. In addition, this motive appeared to positively predict working status after three years. The financial advantages of working and the maintenance of social contacts were the reasons reported most frequently for not taking full retirement, with the financial aspect being a reasonably good predictor for working status after three years. From the interviews and the workshop, five themes were identified as important motives to prolong working life: challenges at work, social contacts, reward and appreciation, health, and competencies and skills. Further, it was brought forward that each stakeholder can and should contribute to the maintenance of a healthy and motivated ageing workforce. Conclusion Based on the findings, it was concluded that measures that promote challenges at work, together with financial stimuli, seem to be promising in order to prolong workforce participation.